INTERTEXTUALITY OF THE SAGAS OF RAGNAR LODBROK BY BEN WAGGONER AND ITS TV-SERIES VERSION: VIKINGS (SYMBOLIC INTERACTIONISM APPROACH) - Restu Wahyuning Asih (UIN Raden Mas Said Surakarta, 2021)
Abstract Mythical and historical stories were mushroomingly adapted into movies. However, intertextuality is proven to be an obstacle in the adaptation process since adaptation might trigger losses on the meaning of the original works.Addressing this issue, this descriptive qualitative research attempts to reveal (1) the types of intertextuality found from the Sagas of Ragnar Lodbrok by Ben Waggoner and its TV-Series Version: Vikings through the characterization of Ragnar Lodbrok, (2) how is intertextuality presented in the Sagas of Ragnar Lodbrok by Ben Waggoner and its TV-Series Version: Vikings through the characterization of Ragnar Lodbrok. Intertextuality theory by Fitzsimmons (2013) and characterization theory by Bernardo (2015) were applied to answer these problems. The data of this research were words, phrases, clauses, sentences, and visualizations, considered to reflect the characters of the story. The data were taken from the Sagas of Ragnar Lodbrok and Vikings TV series. The data were analyzed by employing Spradley’s componential analysis. Symbolic Interactionism approach was applied in this research to reveal how characters were treated as a symbolic meaning in intertextual domain. Derived from the analysis, this research unveils three types of intertextuality namely optional, obligatory, and accidental. The data shows that optional intertextuality is the most common type of intertextuality found from this research. Characterization of Ragnar was intertextually presented through thirteen manners or types with what others say and physical visualization as the recurring types. These findings indicate that a shift on perspective occurs. This shift signifies how Ragnar Lodbrok is differently treated to meet the distinctive features of the media in which the story occurs and the users of the media. Key words: Intertextuality, Ragnar Lodbrok, Characterization, Symbolic Interactionism